Optimalisasi Internet of Things pada Pembelajaran PAUD di Desa Masangan Kulon, Sidoarjo - Aziz, Muhammad Hilmy; Wulansari, Trie Indah (Jurnal Bisnis Indonesia, 2024)
The Internet has transformed into a need that will never be marginalized by the people of Indonesia,including the world of education, which has widely used the Internet as a companion for teaching andlearning activities. The Internet provides countless spaces to explore many things that can bring lifeexperiences, especially for early childhood, who need a lot of insight for the development of sensoryand motor stimuli. This research focuses on how the Internet has a divided impact on optimizing thelearning of Early Childhood Education (PAUD) students that have the potential to be used in learningmedia. The research method will be closely related to qualitative research by emphasizing theobservation aspect. Observation brings researchers to a reality that can be observed by the fivehuman senses, thus allowing the updating of models for the realization of new digital-based learning.This study produces several main things that are the answer to optimizing the use of the Internet inECCE learning. First, the Internet as a means of communication and information provides a newatmosphere related to ECCE student learning, such as distance learning, which is needed to exploremore demonstrations called live streaming of the animal world, the professional world, and the worldof flora. Second, the Internet, as a means of supporting learning, can act as an optimization ofpractical teachings, such as learning about limbs, learning about how to make food, and how to makea game. By optimizing the potential of the Internet in all aspects of learning, ECCE becomes a strongfoundation upon which intellectual human resources are produced.Keywords: Internet of Things; Learning Communication Model; Early Childhood Education